Sea-side resort, Trinidad, B.W.I. - (:unkn) unknown (Unknown, 2011)
The postcard shows a resort near the seaside in Trinidad.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Coasts; Resorts; 1940